EFFICIENT MANAGEMENT OF CURRENCY INVESTMENT PORTFOLIO ON THE EXAMPLE OF DARNYTSYA PHARMACEUTICAL COMPANY - Ж. М. Жигалкевич; С. О. Кольчик (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The presented article explores the investment methodology and offers practical recommendations for the effective management of the foreign currency investment portfolio of the enterprise of the pharmaceutical industry. Based on the use of existing scientific and methodological approaches, including system analysis, statistical methods, risk and profitability analysis, improved methods and models of currency portfolio management were developed. Such tools allow enterprises to increase flexibility, optimize investment decisions and minimize risks, which is especially important in the context of market volatility. The results of the research are of practical importance for pharmaceutical companies, allowing them to optimize the management of currency investment portfolios and increase the efficiency of investments in conditions of global economic uncertainty.